MULTIVIRATE ANALYSIS ON THE STUDENTS’ CHALLENGES ON ONLINE DELIVERY EDUCATION - TAMAYO, RIA; CAUILAN, MARIDEN; BARSABAL, HILARIA (International Journal of Arts, Sciences and Education, 2022)
The study analyzed the challenges on online delivery education among university students of Cagayan State University. It determined the profile of the respondents in terms of age, sex, socio-economic status, educational attainment of the respondents’ parents and the campus they belong. It also identified the academic performance of the respondents. Furthermore, it identified the problems encountered by the respondents during online class along geographical location, adaptability struggle, technical issues, computer literacy, time management and self-motivation. The profile variables of the student-respondents were correlated to their academic performance. The General Weighted Average of the students was the basis for identifying their academic performance. Descriptive correlation design was utilized. Pearson-R correlation was used to determine the relationship of the respondents’ profile and their academic performance and ANOVA was used to compare the problems faced by the students during online when grouped according to campus. It was found out that majority of the respondents’ age ranges from 19-21 years old, female dominated, belonged to the poor family and their academic performance is good. The study concluded that the respondents’ profile variables are contributory factors for their academic performance. The respondents encountered problems along geographical location, adaptability struggle, technical issues, computer literacy, time management and self-motivation. And the problems encountered by the respondents along geographical location, adaptability struggle, technical issues, computer literacy, time management and self-motivation by the students are highly significant to their academic performance.